INTERDIFFUSION OF H2O AND CO2 IN METAMORPHIC FLUIDS AT ~490 TO 690°C AND 1 GPA - Wark D.A.; Watson E.B. (My University, 2004)
Interdiffusion coefficients have been determined for H2O-CO2 mixtures by quantifying the flux of CO2 between two fluid-filled chambers in a specially designed piston-cylinder cell. The two chambers, which are maintained at 1.0 GPa and at temperatures differing by ∼100°C, each contain the XCO2-buffering assemblage calcite + quartz + wollastonite, in H2O. The positive dependence of XCO2 on temperature results in a down-temperature, steady-state flux of CO2 through a capillary tube that connects the two chambers. This flux drives the wollastonite = calcite + quartz equilibrium to the right in the cooler chamber, producing a measurable amount of calcite that is directly related to CO2-H2O interdiffusion rates. Diffusivities calculated from seven experiments range from 1.0 × 10−8 to 6.1 × 10−8 m2/s for mean capillary temperatures between ∼490 and 690°C. The data set can be approximated by an Arrhenius-type relation: D=4.7×10−6exp(–4560/T) m2/s (T in K), which yields values within a factor of 2 of, but slightly lower than, diffusivities estimated by application of the Stokes-Einstein relation.Because rates of H2O and CO2 interdiffusion approach (within 1 to 2 orders of magnitude) rates of heat conduction in rocks, rapid CO2-H2O interdiffusion should be expected in deep-seated fluids wherever gradients in XCO2 are imposed by contrasting mineral assemblages. Considering the small-scale heterogeneity of the crust, strong gradients in XCO2 are probably quite common, particularly where different carbonate-bearing assemblages are juxtaposed or where they are interlayered with carbonate-absent rocks. Cross-layer, diffusive mass transfer of CO2 and H2O may play an important role in driving dehydration and decarbonation reactions, even in the absence of fluid flow.